PERBEDAAN DAMPAK UKGS MANDIRI ANTARA SD ANTONIUS DAN SD PETRA SEMARANG - Irma Haida Yuliana Siregar; Iman Supardan; Sadimin Sadimin (Jurnal Kesehatan Gigi, 2018)
TITLETHE DIFFERENCE IMPACT of  INDEPENDENT UKGS BETWEEN SD ANTONIUS II AND SD PETRA SEMARANGABSTRACTOral Health Program for School Children (UKGS Program) has been implemented by Community Health Center since 1951 but the result isn’t satisfied yet. National research of Health 2013 has found that the dental caries prevalence among children in Indonesia has increased 13,7%. DMF-T index among 12 years old children has increased from 0.91 to 1.4. It means that there are 140 decays among 100 children nowadays. Due to this condition, Dental Nurse Department (JKG) Poltekkes Semarang had tried to implement improvized UKGS Program to a school independently. This study wanted to know the impact among students of SD Antonius and SD Petra which has implemented independent UKGS.This was quantitative descriptive research with cross sectional approach. The samples were 10% of total students of SD Antonius II and SD Petra – 38 students for each school – taken randomly from class I to VI. The data were analyzed by Mann Whitney and Independent T-test.The result showed that non clinically, there was no significant difference on students knowledge (p value 0.697 0.005) but not on Attitude and Action (pvalue 0.024 and 0.000 0.005). Clinically, the significant difference could be seen on OHI-S Index ( p value 0.046) but not on DMF-T and deft Index (p value 0.430 and 0.345). It’s suggested that this research had to be continued to find out the influence of Independent UKGS Program with students satitsfaction.